Biogenesis and Characterization of Pilea-Microphylla Ferric Oxide Nanoparticles - Gaikwad, Deepak; Udekar, Prathmesh; Lohakare, Neelam; Lad, Vishwanath; Naik, Omkar; Patil, Sahil (International Journal of Engineering and Management Research, 2025)
Nanotechnology involves the manipulation of materials at the nanoscale, enabling their application across fields such as environmental remediation, medicine, and engineering. However, conventional nanoparticle synthesis methods often rely on toxic reducing agents like sodium borohydride, posing environmental and health risks. This research focuses on the eco-friendly synthesis of ferric oxide nanoparticles (Fe2O3NPs) using the plant extract Pilea microphylla, a herb rich in bioactive phytochemicals such as quercetin, luteolin, and apigenin derivatives. These phytochemicals act as natural reducing and capping agents, eliminating the need for hazardous chemicals. In this study, Pilea microphylla was processed into an aqueous extract and used to synthesize Fe2O3NPs from ferric nitrate. The reaction mixture was stirred with NaOH and centrifuged to collect the nanoparticles, which were subsequently calcined at 300–400°C. The synthesized Fe2O3NPs were characterized using X-ray Diffraction (XRD) and Field Emission Scanning Electron Microscopy (FESEM) to confirm particle size and morphology. The results demonstrate that plant-based synthesis offers a scalable, cost-effective, and sustainable approach to nanoparticle production, with potential applications in wastewater treatment and environmental remediation.